2015
DOI: 10.1021/acs.est.5b01439
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Deepwater Horizon Crude Oil Burnoff Particulate Matter Induces Pulmonary Inflammation and Alters Adaptive Immune Response

Abstract: The ″in situ burning” of trapped crude oil on the surface of Gulf waters during the 2010 Deepwater Horizon (DWH) oil spill released numerous pollutants, including combustion-generated particulate matter (PM). Limited information is available on the respiratory impact of inhaled in situ burned oil sail particulate matter (OSPM). Here we utilized PM collected from in situ burn plumes of the DWH oil spill to study the acute effects of exposure to OSPM on pulmonary health. OSPM caused dose-and time-dependent cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Our results with the PM extract from the simulated burning of oil are consistent with those of Jaligama et al [] with the OSPM collected during the in situ burns during the DWH event. They showed that the OSPM induced oxidative stress and pulmonary inflammation both systemically and locally as evidenced by increased numbers of macrophages and eosinophils in the lungs of mice.…”
Section: Discussionsupporting
confidence: 92%
“…Our results with the PM extract from the simulated burning of oil are consistent with those of Jaligama et al [] with the OSPM collected during the in situ burns during the DWH event. They showed that the OSPM induced oxidative stress and pulmonary inflammation both systemically and locally as evidenced by increased numbers of macrophages and eosinophils in the lungs of mice.…”
Section: Discussionsupporting
confidence: 92%
“…Exposure to PM from combustion sources has been shown to affect pulmonary immunologic homeostasis and exacerbate respiratory health effects such as asthma [8, 20, 21]. The association between exposure to elevated levels of PM and enhanced susceptibility to respiratory tract infections in children has been documented.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting suspension was subjected to probe sonication on ice to disperse the particles and maintain a suspension free of particulate aggregates. Mice received 50 μl of the resulting suspension via oropharyngeal aspiration as described earlier [ 32 ]. Control mice were administered 50 μl of particle solution (Vehicle).…”
Section: Methodsmentioning
confidence: 99%